Dress and Cultural Difference in Early Modern Europe - Aust, Cornelia; Klein, Denise; Weller, Thomas (Jahrbuch für Europäische Geschichte / European History Yearbook, 2019)
Dress constitutes one of the most obvious and indeed most visual and visible markers of difference. Being very close to the body it becomes part of the daily habitus and an unavoidable means of communication with others. In this volume, we want to follow transcultural perspectives and highlight the multiplicity of differences that are expressed via clothes.